Knowledge of livestock grading and market participation among small ruminant producers in northern Somalia - Wanyoike, Francis N.; Mtimet, Nadhem; Ndiwa, Nicholas N.; Marshall, Karen; Mugunieri, Lawrence Godiah; Warsame, A. (Informa UK Limited, 2015)
This study focused on market participation and producers’ knowledge of the indigenous livestock grading and pricing system applied to small ruminant marketing in Somaliland. Data were collected from a random sample of 144 men and women producers in three livelihood zones: Hawd pastoral, West Golis pastoral and Togdheer agro-pastoral zones. Results confirmed the importance of small ruminants as sources of income in producer households. Knowledge about the grading system was generally widespread, and this was important for market participation. Factors that significantly influenced market participation were number of animals kept, gender of sales/decision maker, age of household head and livelihood zone.